2011
DOI: 10.30970/cma4.0141
|View full text |Cite
|
Sign up to set email alerts
|

Various configurations of F-H pairs in CaF2 crystals

Abstract: The spectral and kinetic parameters of electron-pulse-initiated transient absorption and luminescence of nominally pure CaF 2 crystals were studied using pulsed spectrometry with nanosecond time resolution. The effect of temperature on the formation of defects was studied. It was established that on increasing the temperature F-H pairs and unknown defects are created. Laser-induced change is studied by optical absorption and luminescence due to F-H pairs generated by an electron pulse in CaF 2 .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…For the study of photo-induced changes in the optical transmission of the crystals with the fluorite structure is widely used technique of cascade excitation, when the first pulse (radiation) is making defects, and the second pulse (laser beam),which is delayed for some time, their excitement is produced. Using cascade excitation technique, it was found that the optical stimulation of STE accompanied by some conversion into other configurations of STE [15] or spatially separated in F-H pairs [16,17]. The processes of photo-induced or thermal conversion of defects are described under the mechanism of the hopping movement of interstitial atoms with the rupture in the hole core of STE [18].…”
Section: Discussionmentioning
confidence: 99%
“…For the study of photo-induced changes in the optical transmission of the crystals with the fluorite structure is widely used technique of cascade excitation, when the first pulse (radiation) is making defects, and the second pulse (laser beam),which is delayed for some time, their excitement is produced. Using cascade excitation technique, it was found that the optical stimulation of STE accompanied by some conversion into other configurations of STE [15] or spatially separated in F-H pairs [16,17]. The processes of photo-induced or thermal conversion of defects are described under the mechanism of the hopping movement of interstitial atoms with the rupture in the hole core of STE [18].…”
Section: Discussionmentioning
confidence: 99%